2017
DOI: 10.1186/s40781-017-0126-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on heart rate, blood lactate concentration, packed cell volume and hemoglobin to exercise in Jeju crossbreed horses

Abstract: BackgroundThis study aimed to analyze the on heart rate, blood lactate concentration, packed cell volume (PCV) and hemoglobin (Hb) response after conducting exercise in endurance horses.MethodsA total of 20 healthy 3–9-years-old Jeju crossbreed mares (5.95 ± 2.24 year) of age and 312.65 ± 13.59 kg of weight) currently participating the endurance competition were used. The field tests selected for the experiment was gallop (approximately 8.3 m/s) along the selected 2.5 km course (a natural forest trail, not art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
3
5
0
2
Order By: Relevance
“…The baseline HR reported by Kang and Park () in 3–9‐year‐old Jeju crossbreed mares are similar to the values recorded during the cold‐dry season but lower than those obtained during the hot‐dry season. Merkies et al.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The baseline HR reported by Kang and Park () in 3–9‐year‐old Jeju crossbreed mares are similar to the values recorded during the cold‐dry season but lower than those obtained during the hot‐dry season. Merkies et al.…”
Section: Discussionsupporting
confidence: 74%
“…The baseline HR reported by Kang and Park (2017) in 3-9-year-old Jeju crossbreed mares are similar to the values recorded during the cold-dry season but lower than those obtained during the hot-dry season. Merkies et al (2016) reported higher HR in weaned foals than those recorded in foal donkeys in the current study.…”
Section: Correlation Coefficient Rsupporting
confidence: 75%
“…While packed cell volume can predict the oxygen transportation capacity. These changes are in accord with the earlier finding reported by (Stefansdottir et al, 2014) in horses, their riding assessment and by (Kang and Park, 2017) in horses after endurance exercise. These parameters grant us meaningful information about fitness changes in horses (Piccione et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
“…Thereafter, they were walked to their paddocks within 5 min and left loose in them for the remaining time until completing the total of 30 min set for recovery observation. It is known from other studies that HR recovers more rapidly when horses are walked, and even more rapidly when trotted instead of kept standing [37,38]. Thus, it is likely that the HRrecovery rates of the horses in this study would have been somewhat higher after the 15th minute if they had been walked until the end of the recovery period of 30 min.…”
Section: Discussionmentioning
confidence: 78%